Analysis of Differences in Consumer Perceptions of Service Quality from an Islamic Perspective (Study of Panorama Traditional Markets and Hypermart Modern Markets) - Nana Aprina; Desi Isnaini; Faisal Muttaqin (Sharia Economic and Management Business Journal (SEMBJ), 2024)
The purpose of this research is to determine the differences in consumer perceptions of service quality, namely: the direct evidence dimension (tangibles), the reliability dimension, the responsiveness dimension, the assurance dimension, and the empathy dimension in the traditional market "Panorama ” and the Modern Market “Hypermart”. To test this, researchers used quantitative methods with primary data collection techniques in the form of questionnaires distributed to 200 respondents. The data analysis technique used is an independent sample t-test using the SPSS version 25 program. From the results of the research and discussion, it was found that differences in consumer perceptions of service are found in the dimension of attention (empathy) with a significance value (sig-2-tailed) of 0.003 for the empathy variable. at a significance level of 5% this value is significant because the significance is 0.003 > 0.05 and for the dimensions of tangibles, reliability, responsiveness, and assurance there is no difference in perception because the significance value is greater than 0.05. With this research, it is known that there are differences in perceptions in the empathy dimension and it is hoped that this can become a benchmark for improving service performance.